HackaBIP: Possibilities and challenges of co-producing civic tech in Lisbon's local development - Ana Carolina C. Farias (Cidades, Comunidades e Território)
This study explores the potential of civic hacking to enhance local development in Lisbon, focusing on the hackaBIP civic hackathon as a participatory model for the co-production of digital tools. The research poses the question of how to engage local initiative organisations in civic tech co-production, adopting the civic hackathon as a collaborative methodology and as a basis for designing an information infrastructure for sustainable collaboration. The Lisbon Local Development Strategy BIP/ZIP provided the context for the study, given the need to enhance collaboration and monitoring capacities of its network of actors, as understood under the penta-helix model of social innovation. The results indicate that, despite the potential of civic techs to explore available open data and generate other necessary data, the initiative encountered significant challenges, including power imbalances between community actors and tech developers. Discussions highlight the importance of the ignitor actor in sustaining ongoing collaboration, the need for academic institutions to engage more actively with community initiatives, and the need for local governments to be more responsive. Ultimately, this research argues for the establishment of hackable universities – open and transdisciplinary academic environments that foster dialogue with local initiatives to increase civic engagement and contribute to building hackable cities.